2016
DOI: 10.1016/j.jhydrol.2016.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability of droughts and terrestrial water storage over Lake Chad Basin using independent component analysis

Abstract: 9Lake Chad has recently been perceived to be completely desiccated and almost extinct due 10 to insufficient published ground observations. Given the high spatial variability of rainfall in 11 the region, and the fact that extreme climatic conditions (for example, droughts) could be 12 intensifying in the Lake Chad basin (LCB) due to human activities, a spatio-temporal ap-13 proach to drought analysis becomes essential. This study employed independent component 14 analysis (ICA), a fourth-order cumulant statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 75 publications
7
52
0
Order By: Relevance
“…Maidment et al () in their analysis observed a positive trend in rainfall in the LCB covering the semi‐arid zone of the Logone catchment while Okonkwo et al () also reported a similar trend in the southern part of LCB covering the Sudano zone of the catchment. In a recent study, Ndehedehe et al () also reported an increasing trend in rainfall over the LCB since 1990. In addition, the positive trends in rainfall observed in the catchment are reported to be a global trend (Westra et al , ).…”
Section: Resultsmentioning
confidence: 86%
“…Maidment et al () in their analysis observed a positive trend in rainfall in the LCB covering the semi‐arid zone of the Logone catchment while Okonkwo et al () also reported a similar trend in the southern part of LCB covering the Sudano zone of the catchment. In a recent study, Ndehedehe et al () also reported an increasing trend in rainfall over the LCB since 1990. In addition, the positive trends in rainfall observed in the catchment are reported to be a global trend (Westra et al , ).…”
Section: Resultsmentioning
confidence: 86%
“…The slight increase in lake area is in line with a study which showed improving wet conditions in the last two decades with 2002–2014 described as the wettest period. The authors attributed this to increasing rainfall in the area and the lack of any major long-term drought besides the usual seasonal fluctuations [51]. Lake Chad’s average area from 2003–2016 was estimated to be 1694 km 2 with a standard deviation of about 233.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in estimated lake area could also be partially explained by the slight increase in altimetric lake levels (Figure 2a). Between 2008 and 2014, there was a yearly increase of about 0.4 m/year in altimetry lake levels [51]. Lake area estimates also match with an increasing agricultural productivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations